Thyrotropic Axis and Disorders of Consciousness in Acquired Brain Injury: A Potential Intriguing Association? - Mele, Chiara; De Tanti, Antonio; Bagnato, Sergio; Lucca, Lucia Francesca; Saviola, Donatella; Estraneo, Anna; Moretta, Pasquale; Marcuccio, Laura; Lanzillo, Bernardo; Aimaretti, Gianluca; Nardone, Antonio; Marzullo, Paolo; et al. (Frontiers in Endocrinology, 2022)
Purpose A potential involvement of thyrotropic axis in influencing the state of consciousness could be hypothesized. We aimed at investigating thyroid function tests as predictors of disorders of consciousness (DoC) and relating recovery in a large cohort of patients with DoC secondary to acquired brain injury (ABI). Methods This retrospective, multicenter, cohort study included 151 patients with DoC following ABI, consecutively admitted for a 6-month neurorehabilitation program. Data on etiology of brain injury, evolution of DoC, disability and rehabilitation assessments, and death during rehabilitation were collected at baseline and on discharge. Thyroid function tests (serum TSH, fT4 and fT3 levels) were assessed on admission in all patients and at final discharge in 50 patients. Results Lower baseline TSH levels and greater TSH increments (ΔTSH) after neurorehabilitation predicted a favorable change in DoC independent of age, sex, BMI, etiology of brain injury and initial DoC subtype (TSH: OR=0.712, CI 95% 0.533-0.951, p=0.01; ΔTSH: OR=2.878, CI 95% 1.147-7.223, p=0.02). On the other hand, neither fT4 nor fT3 or their variations appeared to play any role on DoC changes after 6-months inpatient neurorehabilitation. A lower magnitude of ΔfT4 acted as a strong predictor of improved functional disability level (β=0.655, p=0.002) and cognitive functions (β=-0.671, p=0.003), implying that smaller changes in fT4 were associated with higher outcomes. Conclusions Serum TSH levels assessed in the subacute post-ABI phase and its variation during neurorehabilitation could represent a potential biomarker of DoC evolution, while variations in fT4 levels seem to be associated with rehabilitation and cognitive functions. Further studies are needed to investigate the mechanisms underlying these associations.